Freudian Approach to Psychological Condition and Behavior Through the Characters of Mr and Mrs White - Febriandy, Agustio; Rahmawati, Irma (Aksara: Jurnal Bahasa dan Sastra, 2024)
This study delves into the psychological underpinnings of W.W. Jacobs' 1902 short story "The Monkey's Paw," exploring the intersection of human psychology and literary themes. The purpose of this research is to analyze the short story "The Monkey's Paw" characters' psychological behavior. This research uses a qualitative methodology and applies Sigmund Freud's theory of the Id, Ego, and Superego to analyze the characters Mr. and Mrs. White using non-numerical data. The objectives are to examine how the Id, Ego, and Superego influence individual behavior and actions; evaluate Mr. White's ability to manage his psychological mind; and determine the psychological profiles of Mr. White as an Ego character and Mrs. White as an Id character. The findings reveal significant psychological dynamics shaping the characters' behaviors and decisions. Mr. White's predominance of Ego allows him to regulate his psychological responses, contrasting with Mrs. White's Id-driven actions. In conclusion, the goal of this research is to improve knowledge of psychology, psychoanalysis, and the motivations behind people's acts and behaviors., psychoanalysis, and the motivations behind people's acts and behaviors. Keywords: Freudian Psychology; Literary Analysis; Id, Ego, and Superego.